Pengaruh Pelatihan Pancacara Temuan Makna Terhadap Penurunan Depresi Pada Lanjut Usia - Setiawan, Arif Budi, Dr. Nisa Rachmah N.A., M.Si, Psi, Dr. Eny Purwandari, M.Si (2016)
The condition of elderly are already experiencing a decline in some aspects of his life. These conditions will grow when elderly are in far away from their families. Logotherapy is one approach to psychotherapy treatment depression sufferers , especially for seniors who are less effective given the cognitivebehavior psychotherapy because of problems at the level of education. Logotherapy are given in the form of training that has been adapted to the cultures of Indonesia, namely Pelatihan Pancacara Temuan Makna Berdasar Konsep Logoterapi. The purpose of this research is to know the effect of Pelatihan Pancacara Temuan Makna Logotherapy Themed to reduce the degree of depression in elderly at Social Recidential Dharma Bhakti Surakarta. Design research is experimental research with quota sampling purposive. Measuring instrument used is the Geriatric Depression Scale 15 (GDS15) special for elderly. The characteristics of the subject was elderly aged 60 - 85 years, educated in elementary school up to high school, score GDS15 in the category of depression. Data analysis using the techniques of analysis of non-parametric Wilcoxon signed rank test and Mann Whitney U with SPSS for Windows version 16. The conclusion from this study is there is the effect of Pelatihan Pancacara Temuan Makna Logotherapy Themed to reduce the degree of depression in elderly.